Duhuo Jisheng Decoction inhibits SDF-1-induced inflammation and matrix degradation in human degenerative nucleus pulposus cells in vitro through the CXCR4/NF-κB pathway - LIU Zong-chao; WANG Zhen-long; HUANG Chen-yi; FU Zhi-jiang; LIU Yong; WEI Zhang-chao; LIU Shi-gui; MA Chuan; SHEN Jie-liang; DUAN Dayue Darrel (Acta Pharmacologica Sinica, 2018)
Abstract Lower back pain (LBP) is the most common disease in orthopedic clinics world-wide. A classic Fangji of traditional Chinese medicine, Duhuo Jisheng Decoction (DHJSD), has been proven clinically effective for LBP but its therapeutic mechanisms remain unclear. We hypothesized that DHJSD might relieve LBP through inhibiting the exaggerated proinflammatory cytokines and extracellular matrix (ECM) degradation. Thus, we studied the effects of DHJSD on stromal cell-derived factor-1 (SDF-1)-induced inflammation and ECM degradation in human nucleus pulposus cells (hNPCs). The primary hNPCs were isolated from either degenerated human intervertebral disc (HID) of LBP patients or normal HID of lumbar vertebral fracture patients, and cultured in vitro. The cells were treated with SDF-1 (10 ng/mL) and subsequently with different concentrations (100–500 μg/mL) of DHJSD for 24 h, respectively. We found that application of DHJSD significantly antagonized the SDF-1-induced production of proinflammatory cytokines and reduction of aggrecan and type II collagen in the hNPCs. DHJSD also markedly reduced the SDF-1-induced increase of CXCR4 and p-p65 and inhibited the nuclear translocation of p65 in the hNPCs. DHJSD, CXCR4-siRNA, and NF-κB inhibitor (BAY11-7082) caused the same inhibition of exaggerated proinflammatory cytokines in the SDF-1-treated hNPCs. These results provided compelling evidence that DHJSD may inhibit the generation of proinflammatory mediators and ECM degradation of HID through an orchestrated targeting at multiple molecules in the SDF-1/CXCR4/NF-κB pathway, thus offered novel mechanistic insights into the clinical effectiveness of DHJSD on LBP.